Literature Riview: Analisis Capaian KB Aktif dan Kontrasepsi pada Masa Pandemik Covid-19 - Anggit Yanuaristi; Dean Wahjudi Satyaputra; Lelly Yuniarti (UNISBA Press, 2023)
Abstract: The government established a PSBB policy in 2020 to break the chain of distribution of COVID-19 by limiting people's mobility towards social contact, this has an impact on limited access to health services. This study aims to examine the achievements of active family planning and contraception programs during a pandemik by using the literature review method to identify published literature using relevant keywords. Based on the literature review produced, active KB acceptors decreased during a pandemik, contraceptive methods that experienced a decrease included MOP, pills, injections and MOW. Contraceptives that have increased in IUDs, Implants and Condoms. In conclusion, the results of active family planning decreased due to COVID-19, the distribution of contraceptives was made easier for the community and family planning services were further improved to prevent the